2021
DOI: 10.1002/advs.202100014
|View full text |Cite|
|
Sign up to set email alerts
|

KAT6A Acetylation of SMAD3 Regulates Myeloid‐Derived Suppressor Cell Recruitment, Metastasis, and Immunotherapy in Triple‐Negative Breast Cancer

Abstract: Aberrant SMAD3 activation has been implicated as a driving event in cancer metastasis, yet the underlying mechanisms are still elusive. Here, SMAD3 is identified as a nonhistone substrate of lysine acetyltransferase 6A (KAT6A). The acetylation of SMAD3 at K20 and K117 by KAT6A promotes SMAD3 association with oncogenic chromatin modifier tripartite motif-containing 24 (TRIM24) and disrupts SMAD3 interaction with tumor suppressor TRIM33. This event in turn promotes KAT6A-acetylated H3K23-mediated recruitment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…The analysis of the expression profile (GSE108242) obtained from the KAT6A gene knockdown model revealed that the expression of this gene was closely associated with several cancer hallmark-related pathways ( Figure 6(a) ). G2M signal checkpoint pathway (HALLMARK_G2M_CHECKPOINT) was found upregulated after the knockdown of KAT6A ( Figure 6(b) ), whereas the TGF- β signaling pathway was inhibited after KAT6A knockdown ( Figure 6(c) ); this observation was also supported by previous analysis [ 23 ].…”
Section: Resultssupporting
confidence: 86%
“…The analysis of the expression profile (GSE108242) obtained from the KAT6A gene knockdown model revealed that the expression of this gene was closely associated with several cancer hallmark-related pathways ( Figure 6(a) ). G2M signal checkpoint pathway (HALLMARK_G2M_CHECKPOINT) was found upregulated after the knockdown of KAT6A ( Figure 6(b) ), whereas the TGF- β signaling pathway was inhibited after KAT6A knockdown ( Figure 6(c) ); this observation was also supported by previous analysis [ 23 ].…”
Section: Resultssupporting
confidence: 86%
“…Overexpression of YWHAE increases the proliferation, migration and invasion ability of breast cancer cells [ 18 ]. KAT6A promotes SMAD3 binding to oncogenic chromatin modifier TRIM24 and disrupts its interaction with the tumor suppressor TRIM33, which lead to the tumor cell metastasis in breast cancer [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…SMAD3 is identified as a non-histone substrate of lysine acetyltransferase 6A (KAT6A). Targeting KAT6A in combination with anti-PD-L1 therapy in TNBC-bearing xenografts models reduced MDSC recruitment, significantly alleviated metastasis potential and increased overall survival ( 84 ). For advanced prostate cancer (PCa), the majority of patients are resistant to ICB, due to the accumulation of MDSCs.…”
Section: Synergistic Roles Of Icb and Targeting Mdscsmentioning
confidence: 99%